PENINGKATAN KEBUGARAN JASMANI SISWA MELALUI AKTIVITAS FISIK RINGAN DALAM PEMBELAJARAN PJOK - Tahta Krisna Wira Prakosa; Sasminta Christina Yuli Hartati (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
During the Covid-19 pandemic, health is important for daily human activities. One of the ways to maintain health is to improve physical fitness in the body through physical activity, one of which is through PJOK learning. This study was to determine the effect of light physical activity in learning PJOK on the level of physical fitness of students. This study uses an experimental method with One Group Pretest-Posttest design which will be concluded later. The sampling technique used was purposive sampling with a population of all class IX students at SMP Negeri 2 Kawedanan Magetan for the 2021/2022 academic year. The selected class is class IX A which has the same criteria for physical activity in PJOK learning. This research consists of three stages, the first is pre-test, the second is giving treatment in the form of PJOK learning, and the third stage is post-test. The instrument to measure the pre-test and post-test scores in this study was the multi-stage fitness test. Data analysis in this study used normality, homogeneity and t-test techniques. The results of this study were an increase in light physical activity in learning physical education, sports and health on the level of physical fitness of students. It is evident from the tcount (40.96) > ttable (1.720), the pre-test result was 25.89 ml/kg/minute and the post-test was 28.96 or an increase of 11%. The conclusion of this study is that there is an increase in students' physical fitness through light physical activity in PJOK learning.